Development of a family product usability model for older Malaysians - Zareei, Hassan (2015)
Products, systems, and environments should be designed based on the needs and capabilities of the elderly. Various usability models including intelligence usability model, individual and integrated usability model, and multi-level hierarchical model are currently available but none provide an integrated evaluation and fail to assess usability in various products at the same time. Since the elderly are more engaged with their daily living activities, the usability of the family products of the daily living should be considered. The aim of this study was to develop an integrated usability model to measure and rank common family of products based on the level of usability. This model can assist the elderly to identify user friendly products and provide a guideline for the producers to design and improve their products based on the needs of the elderly. Seven Focus Group Discussions (FGD) were conducted to identify the characteristics affecting the usability of each related family of products based on Instrumental/ Enhanced Activities of Daily Living (I/EADL). The FGD sessions revealed seven I/EADL categories as well as six essential family of products. A total of 126 characteristics affecting the usability of I/EADL family products were generated based on the FGDs, market survey, and literature review of the current family of products. A questionnaire was then designed based on these usability characteristics. A total of 303 interviews were conducted among the elderly in the state of Selangor based on stratified random sampling from three main ethnic groups in Malaysia. The interviews revealed that the most frequently used I/EADL family of products were Television (TV) (95%), TV Remote (TVR) (91.7%), Rice Cooker (RC) (82.3%), Mobile Phone (MP), and Washing Machine (WM) (72.6%) while Online Transactions (97.4%), Internet/E-mail (89.4%) and ATM (71.3%) posed handling problems to the elderly. Safety features and durability were found to be the most crucial criteria of all family of products except for ATM, WM, and TVs. Ease of learning criterion was highly ranked for ATM and TV, while ‘Easy of cleaning parts’ was found to be the most important criterion for WM. Factor analysis was carried out to identify the number of latent factors for all the products. The relative weights for the extracted factors were then evaluated by six experts using Group-AHP technique. ‘Progressive feedback and alert’ for ATM, ‘adjustability to user needs and abilities’ for MP, ‘ease of operation’ for HT, WM, EI, VC, and TV, ‘ease of use’ for CO and TVR, and ‘durability and safety features’ for RC was weighted most. A total of 60 products representing 10 family of products were assessed by five respondents. The usability index for each member of the family of product was then obtained by Group-AHP/TOPSIS which was used to select the best product within each family based on the usability index. Whirlpool WM and Side-Cutter CO had the highest usability index. None of the four common designs of HT complied with the usability factors indicating that the design of current HT family is unsuitable for the elderly for communication. The design of products should be based on the identified weighted factors to provide more usable products for the elderly.